Contemporary Challenges in the Digitization of Companies' Foreign Trade Activities - A.B. Mirkhujaev (Journal of Indonesian Management, 2024)
Digitalisation enables companies to significantly reduce costs associated with their foreign trade activities. The implementation of digital technologies simplifies the organization and execution of foreign trade operations, thereby enhancing the competitiveness of exported goods. Furthermore, the widespread adoption of digital technologies within companies' foreign trade activities is driving the emergence of new trends in both the supply and demand of goods. This shift allows for the substitution of expensive resources with more cost-effective alternatives, reduces labour costs, and uncovers previously untapped resources in the production process. The article explores and substantiates the potential benefits of digitalization in the foreign trade activities of companies.